Heat and Mass Transfer during High-Speed Acceleration of Steel Reference Node through the Channel of Ballistic Booster Complex; Journal of Engineering Thermophysics; Vol. 27, No. 3 - Guskov A. V. Anatoly Vasiljevich; Lider A. M. Andrey Markovich; Maksimov V. I. Vyacheslav Ivanovich; Milevsky K. E. (2018, 2018)
Title screen